2018
DOI: 10.1371/journal.pone.0198698
|View full text |Cite|
|
Sign up to set email alerts
|

Clinic-based evaluation study of the diagnostic accuracy of a dual rapid test for the screening of HIV and syphilis in pregnant women in Nigeria

Abstract: BackgroundScreening pregnant women for HIV and syphilis is recommended by WHO in order to reduce mother-to-child transmission. We evaluated the field performance, feasibility, and acceptability of a dual rapid diagnostic test (RDT) for HIV and syphilis test in antenatal clinic settings in Nigeria.Methods and findingsParticipants were recruited at 12 antenatal clinic sites in three states of Nigeria. All consenting individuals were tested according to the national HIV testing algorithm, as well as a dual RDT, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 10 publications
4
25
0
Order By: Relevance
“…The positive percent agreement differed from that of Olugbenga et al . [ 21 ] but agreed with the negative percent agreement probably due to the four discordant results in this study. Besides, Olugbenga et al .…”
Section: Discussionsupporting
confidence: 85%
“…The positive percent agreement differed from that of Olugbenga et al . [ 21 ] but agreed with the negative percent agreement probably due to the four discordant results in this study. Besides, Olugbenga et al .…”
Section: Discussionsupporting
confidence: 85%
“…In the case of vector-borne diseases such as malaria and dengue, RDTs are also being implemented (6,7,37). Besides the HIV RDTs, the sensitivity and specificity of SD and WL for ChD are similar to or even higher than those of other RDTs used to diagnose other infections (27,(35)(36)(37)(38)(39)(40)(41).…”
Section: Downloaded Frommentioning
confidence: 99%
“…The sensitivity and specificity of non-laboratory staff correctly identifying cryptococcal antigen were 100% in both studies. Additionally, syphilis testing by non-laboratory staff using the dual HIV/syphilis rapid diagnostic test had an agreement of 0.666 (0.358–0.974) and a specificity of 99.9% (95% CI: 99.8–100%) compared to when compared to laboratory technicians [44]. Furthermore, nursing staff successfully tested external quality assurance panels using syphilis rapid tests with a sensitivity and specificity over 90% [16,47].…”
Section: Resultsmentioning
confidence: 99%
“…Point-of-care viral load testing was found to be easy, or very easy, to use by all non-laboratory staff, while 85% of questionnaire respondents indicated that point-of-care viral load testing was suitable or very suitable for non-laboratory staff [38]. Ninety percent of non-laboratory staff identified that a syphilis rapid diagnostic test was easy to use [16], while antenatal care staff scored the dual HIV/syphilis rapid diagnostic test 2.41 (out of 3) for ease of use and 2.27 (out of 3) for ease of interpretation [44].…”
Section: Resultsmentioning
confidence: 99%